The Economical Factors of Employment and Unemployment - Valentinavičius, Stasys (Ekonomika, 2001)
This article analyses the factors, which help to increase employment in the developed countries. The main focus of this study covers: economic growth and trends of employment in the sectors of economy, level of labour costs, flexibility of the labour market control and rate of innovation (implementation of new technologies).